The Relationship Between Parental Smartphone Use Duration and the Incidence of Stunting in Children in Medan City - Wutama, Kevin; Pratama, Irza Haicha; Fadillah, Qori; Mastura, Indira Ade (CV. Publikasi Indonesia, 2025)
Stunting remains a major public health problem in Indonesia, with multidimensional impacts ranging from impaired physical growth to reduced human capital quality. Socioeconomic status, parental education, and parenting practices are recognized determinants, but the role of digital behavior, particularly smartphone use, remains underexplored. This study aims to analyze the association between parental smartphone use duration and stunting among children in Medan City. An analytical observational study with a case-control design was conducted involving 124 respondents (62 cases, 62 controls) selected through purposive sampling. Data were collected using sociodemographic questionnaires and the Smartphone Addiction Scale – Short Version (SAS-SV). Statistical analysis employed Chi-Square tests and Odds Ratio estimation. Most case respondents had a high school education (51.6%) and a family income of IDR 1,000,000–3,000,000 (64.5%), while control respondents were predominantly university graduates (88.7%) with incomes exceeding IDR 5,000,000 (54.8%). Smartphone addiction was more prevalent in the case group (71.0%) than in controls (21.0%). A significant association was found (p < 0.001), with OR = 9.214 (95% CI: 4.053–20.948). Excessive parental smartphone use is significantly associated with stunting in children, highlighting the need for preventive interventions that address digital behavior as an emerging risk factor.